Kepemimpinan dan Kontrol Kebijakan: Pembentukan Budaya Anti Korupsi di Perguruan Tinggi - Bach Yunof Candra (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
Anti-corruption education is very important in building an anti-corruption culture in universities by instilling integrity values in students and staff in universities, increasing awareness and understanding of corruption, shaping anti-corruption attitudes and behaviors in students and staff, and encouraging active student participation in fighting corruption. Anti-corruption education can help improve the quality of education and the image of universities in society, form young people who have anti-corruption attitudes and behaviors and support the National Movement for Mental Revolution program. The purpose of this study is to analyze leadership strategies applied in controlling policies to form an anti-corruption culture at Sekolah Tinggi Ilmu Tarbiyah (STIT) Ya'mal Tangerang. The data collection techniques used in this study were interviews, observation, and documentation. There are forms of intellectual corruption in universities that need to be prevented by systemic, planned, and science-based efforts. Universities need to make anti-corruption education one of the courses, teach anti-corruption culture through student organizations, and instll integrity values through systematic requirements in all aspects of campus and college life.